The effect of melatonin on rat soleus muscle treated with carbon tetrachloride - VURAL, Duygu Fevziye; MUTLU EYİSON, Hatice; ÖZERKAN, Dilşad; CEBESOY, Suna (Ankara University, 2022)
Antioxidants are known to restrains various tissue damage caused by the administration of carbon tetrachloride (CCl4). This study examined whether melatonin (MEL), a molecule known to have antioxidant properties, has a protective effect on the rat soleus muscle, where toxic damage is caused by the application of CCl4. In the study, eighteen albino-type male Wistar rats were used and divided into three groups as Control Group (group 1), CCl4 group (group 2) and CCl4 + MEL group (group 3). End of the 12 weeks, blood samples were taken as intracardiac from the rats under ketamine/rompun anesthesia, and the soleus muscles of the rats were removed. Tissue samples were subjected to routine preparation procedures for light microscopy. Sections 5 µm thick taken and stained with hematoxylin-eosin (HE) for histopathological examinations and Masson’s Trichrome stain for fibrosis formations. In conclusion, the CCl4 group displayed muscular hypertrophy, fiber orientation dysfunction and atrophy in some areas. In addition, fibrosis was spotted around the venous and nerve plexuses. In contrast to the CCl4 group, the melatonin group displayed no fibrosis and maintained tissue integrity. Therefore, when comparing CCl4+MEL and CCl4 groups, it was observed that melatonin had a stabilizing or even curative effect on the injuries.
Keywords: Skeletal muscle; soleus muscle; melatonin; CCl4; Structural Biology; Yapısal Biyoloji; 3. Good health